Pengaruh Disiplin Kerja, Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan CV Sumber Mulyo Furniture Kabupaten Klaten - Yohana Imanda Dewi; Asih Handayani (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of work discipline, leadership, and compensation on employee performance at CV. Sumber Mulyo Furniture, Klaten Regency. Data collection in this study used questionnaires distributed to respondents. The sample in this study consisted of 50 employees at CV. Sumber Mulyo Furniture, Klaten Regency, using saturated sampling. The analytical methods used in this study were descriptive analysis, multiple linear regression analysis, t-test, F-test (model fit test), and coefficient of determination (R2) test. The  results indicate that work discipline significantly influences employee performance at CV. Sumber Mulyo Furniture, Klaten Regency (p-value = 0.000 < 0.05). Leadership significantly influences employee performance at CV. Sumber Mulyo Furniture, Klaten Regency (p-value = 0.003 < 0.05). Compensation significantly influences employee performance at CV. Sumber Mulyo Furniture, Klaten Regency (p-value = 0.001 < 0.05).